Negro abolitionist literature of the ante-bellum period - Anderson, Ruth (My University, 1967)
Negro literature in the ante-bellum period had as its main goals promoting emancipation of the slaves and protesting disenfranchisement of the free Negroes. To achieve these goals, it was necessary to disprove the widely-held concept of natural inferiority of the Negro race. Negro authors in their writings attempted to prove that their race was equal to their white countrymen in intelligence, abilities, and talents, and was as loyal, responsible, and patriotic. They endeavored to show that Negroes had made worth-while contributions to the development and establishment of the United States as a nation and thus were deserving of the full rights and privileges of American citizenship. This paper surveys some of this literature and discusses in detail four examples: an essay, poetry, a history, and an autobiography, to determine whether and how and if the authors fulfilled their purpose--to further abolition and enfranchisement for their race.
Keywords: Abolitionists -- United States; American literature -- African american authors -- History and criticism; Slavery -- United States -- Controversial literature